GAMBARAN RISIKO PREDIABETES, AKTIVITAS FISIK, PERILAKU SEDENTARI, DAN POLA MAKAN KARYAWAN DI PERUSAHAAN â€œXâ€ - Destu Montius Lokononto, Ardy (Fakultas Psikologi - Universitas Teknologi Sumbawa, 2019)
Diabetes starts to attack the productive age group becomes a new phenomenon that needs to be anticipated. This research is a quantitative descriptive study with the aim of knowing the prediabetes status, the level of physical activity, the frequency of consuming fruits and vegetables, level of social support for Company ?X? employees in Jakarta. Total participants were 64 employees. Data obtained using questionnaires and Focus Group Discussion (FGD). Quantitative data were analyzed using univariate analysis. The prediabetes risk of employees is still relatively low (60.94%), only eight employees have high physical activity (12.50%), 47 participants (73.44%) have an average sitting duration of more than six hours per week, high consumption of white rice (92.18%), low consumption of fruit (34.38%), high consumption of sweet drinks (59.38%), and 53 employees claimed to routinely receive social support from people closest to consume fruit or vegetables. As a preventive, intervention programs are needed to increase physical activity, reduce the duration of sitting, encourage healthy eating patterns, and strengthen social support.